Range : how generalists triumph in a specialized world - "Epstein, David" (London, 2019)
Plenty of experts argue that anyone who wants to develop a skill, play an instrument, or lead their field should start early, focus intensely, and rack up as many hours of deliberate practice as possible. If you dabble or delay, you?ll never catch up to the people who got a head start. But a closer look at research on the world?s top performers, from professional athletes to Nobel laureates, shows that early specialization is the exception, not the rule.